The Mechanism of Land Title Certificate Revocation: Between Administrative Authority and Judicial Decisions - Raden Roro Indria Hetti Damayanti; Sulani Sulani; Rahayu Mardikaningsih (Bulletin of Science, Technology and Society, 2026)
This research discusses the cancellation of land rights certificates as a product of state administrative decisions based on laws and regulations in the land sector. The main focus of the research is to analyze the juridical basis for the cancellation of certificates, the administrative mechanism of cancellation, the authority of the State Administrative Court in cancellation disputes, as well as the legal consequences and administrative responsibility for the cancellation of certificates. This normative legal research uses statutory, conceptual, and case approaches with primary and secondary legal materials analyzed qualitatively through grammatical and systematic interpretation. The results of the research indicate that the parameters of administrative and juridical defects in implementing regulations still give rise to differing interpretations and legal uncertainty. The administrative mechanism of cancellation involves a complex procedure with an imperative five-year time limit. The State Administrative Court has the authority to adjudicate cancellation disputes, but its decisions require further administrative actions. The National Land Agency bears administrative responsibility and potential civil liability for errors in certificate issuance. This research recommends the refinement of cancellation parameters and the strengthening of control mechanisms.